Kinematografia w Kurdystanie. Obraz Kurdów w filmach Bahmana Ghobadiego - Szymczak, Jakub (Studia Azjatystyczne, 2015)
Cinematography can be used as a weapon in the battle for identity. Kurdish people are in a constant need to reinvent their national identity. Some of them use cinema as a tool to tell their stories in order not to be forgotten. One of them – a critically acclaimed director from Iran, Bahman Ghobadi is known especially for his cinematic contribution to the Kurdish issue. The article briefly depicts the history of Kurdish cinema and describes in detail the image of Kurds in Bahman Ghobadi's first four feature films - A Time for Drunken Horses (2000), Marooned in Iraq (2002), Turtles Can Fly (2004) and Halfmoon (2006). All these films are not only great pieces of art, full of symbolic images, but they also contain a complex image of the Kurdish nation. Ghobadi uses his camera to tell stories of small, local communities displaced between Iran, Iraq and Turkey, who struggle to maintain their own culture and dignity.